Peranan Zat Pengatur Tumbuh dalam Perbanyakan Tanaman melalui Kultur Jaringan - Endang Gati Lestari (Jurnal AgroBiogen, 2011)
The Role of Growth Regulator in Tissue Culture PlantPropagation. Endang G. Lestari. In plant tissue culture,growth regulator has significant roles such as to control rootand shoot development in the plant formation and callusinduction. Cytokinin and auxin are two prominent growthregulator. Cytokinin consists of BA (benzil adenin), kinetin(furfuril amino purin), 2-Ip (dimethyl allyl amino purin), andzeatin. While auksin covers IAA (indone acetic acid), NAA(napthalene acetic acid), IBA (indole butiric acid) 2.4-D (2.4-dicholophenoxy acetic acid), dicamba (3,6 dicloro-O-anisicacid), and picloram (4-amino 3,5,6-tricloropicolinic acid).The emphasis of plant growth purposes decide the use ofgrowth regulator. Cytokinin is applied mainly for the purposeof shoot, while auxin is mainly used for the purpose of rootand callus. The application of growth regulator application isvaried, depending on the genotype and physiologicalcondition of the plant. The existence of a certain growthregulating substances can enhance growth regulator activityof other substances. The type and concentration of theappropriate growth regulators for each plant is not the samebecause it depends on the genotype and physiologicalcondition of plant tissue. However so often both arefrequently required depend on the ratio/ratio of auxincytokines or vice versa. The existence of a certain growthregulating substances can enhance growth regulator activityof other substances. The type and concentration of theappropriate growth regulators for each plant is not the samebecause it depends on the genotype and physiologicalcondition of plant tissue. For the propagation, multiple andadventive shoots along with embriosomatic formation couldbe applied. The seedling is obtained from one somatic cell.Here, strong auxin, such as dicamba and picloram 2.4-D, isutilized for callus production. For this reason, seedling perunit could be produced more than that of organogenesis.